2012
DOI: 10.1371/journal.pone.0047825
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibition of KCa3.1 Channels Activity Reduces Cell Motility in Glioblastoma Derived Cancer Stem Cells

Abstract: In the present study we evaluated the expression of the intermediate conductance calcium-activated potassium (KCa3.1) channel in human glioblastoma stem-like cells (CSCs) and investigated its role in cell motility. While the KCa3.1 channel is not expressed in neuronal- and glial-derived tissues of healthy individuals, both the KCa3.1 mRNA and protein are present in the glioblastoma tumor population, and are significantly enhanced in CSCs derived from both established cell line U87MG and a primary cell line, FC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
60
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 57 publications
3
60
0
Order By: Relevance
“…In accordance with these in vitro data is the observation that the IK inhibitor TRAM-34 blocks the brain infiltration by xenografted human glioblastoma cells in orthotopic mouse models (36). High IK channel expression has been associated with upregulation of "stemness" markers (8), and the glioblastoma "stem" cells have been suggested to express a highly migratory phenotype and to be primarily responsible for brain invasion (37,38). As a matter of fact, IK channels have been demonstrated to mediate the migration of neuronal precursor cells, so-called neuroblasts, along the rostral migratory stream to become interneurons in the olfactory bulb of normal adult mouse brain (39).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…In accordance with these in vitro data is the observation that the IK inhibitor TRAM-34 blocks the brain infiltration by xenografted human glioblastoma cells in orthotopic mouse models (36). High IK channel expression has been associated with upregulation of "stemness" markers (8), and the glioblastoma "stem" cells have been suggested to express a highly migratory phenotype and to be primarily responsible for brain invasion (37,38). As a matter of fact, IK channels have been demonstrated to mediate the migration of neuronal precursor cells, so-called neuroblasts, along the rostral migratory stream to become interneurons in the olfactory bulb of normal adult mouse brain (39).…”
Section: Discussionsupporting
confidence: 61%
“…Notably, IK channels are low expressed or even absent in human astrocytes (7) but upregulated during neoplastic transformation and malignant progression of the glioma (8). This suggests a specific function of these channels in glioblastoma tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Ion currents inherent in malignant glioma cells have been increasingly reported to influence the behavior of these cells [2][3][4][5][6][7][8][9][10]. Specifically, numerous reports demonstrated that any perturbations of functional expression in intermediate-conductance Ca 2+ -activated K + (IK Ca ) channels enriched in glioma cells or other types of neoplastic cells are capable of interfering with invasiveness or progression of malignant tumors [4,5,[11][12][13][14][15][16]. Alternatively, oxaliplatin (OXAL) belongs to a family of platinum-based chemotherapeutic compounds and is one of the most active drugs in many types of solid tumors encompassing gliomas [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The results presented herein lead us to propose that the perturbation by OXAL of IK Ca channels is another intriguing mechanism through ability of this drug and its structurally related compounds to interfere with the proliferative activity of glioma cells, if similar findings occur in vivo. The data also raise the possibility of the OXAL actions on other types of neoplastic cells in which IK Ca (or K Ca 3.1) channels are functionally expressed [5,8,[13][14][15]20].…”
Section: Introductionmentioning
confidence: 99%
“…For extensive in-depth reviews, we refer the interested reader to Félétou et al (2010), Wulff and Castle (2010), and Wulff and Köhler (2013). Considering the patho-mechanistic roles of the channels, blockers of K Ca 3.1 channels have emerged as potential drug candidates for the treatment of sickle-cell disease (Ataga and Stocker, 2009), immunosuppression (Wulff and Castle, 2010), asthma (Van Der Velden et al, 2013), fibrosis , atherosclerosis (Toyama et al, 2008), and cancer (Ruggieri et al, 2012;D'Alessandro et al, 2013). Positive-gating modulators (activators) of K Ca 3.1, such as naphtho [1,2-d]thiazol-2-ylamine (SKA-31) (Sankaranarayanan et al, 2009) and 5-methylnaphtho [2,1-d]oxazol-2-amine (SKA-121) (Coleman et al, 2014), may improve endothelium-dependent vasodilation and lower blood pressure (Sankaranarayanan et al, 2009;Köhler et al, 2010;Damkjaer et al, 2012;Mishra et al, 2013;Radtke et al, 2013;Wulff and Köhler, 2013).…”
Section: Introductionmentioning
confidence: 99%